1969
DOI: 10.1111/j.1469-7998.1969.tb02157.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the egg shells of the Gaviiformes, Procellariiformes, Podicipitiformes and Pelecaniformes

Abstract: Egg shells of the Gaviiformes, Procellariiformes, Podicipitiformes and Pelecaniformes have been studied using general inspection, chemical analysis, histological and plastic embedding techniques. In all four orders there is a true shell consisting of large crystals having their origin at the surface of the membrane. In the Gaviiformes and Procellariiformes, the true shell is then covered with a cuticle, while in the Podicipitiformes and Pelecaniformes (except for the Phaethontidae) there is a calcareous cover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…A pore provides direct connection between the outside environment and the spaces between the cones. Tyler (1964bTyler ( , 1965Tyler ( , 1966bTyler ( , 1969 and Tyler & Simkiss (1959b) have studied pore structure in different types of birds by the technique of making casts (Tyler 1956) and shown that different bird groups have pore channels of different shape and structure.…”
Section: Poresmentioning
confidence: 99%
See 2 more Smart Citations
“…A pore provides direct connection between the outside environment and the spaces between the cones. Tyler (1964bTyler ( , 1965Tyler ( , 1966bTyler ( , 1969 and Tyler & Simkiss (1959b) have studied pore structure in different types of birds by the technique of making casts (Tyler 1956) and shown that different bird groups have pore channels of different shape and structure.…”
Section: Poresmentioning
confidence: 99%
“…Thiswould suggest that, although the surface layer is laid down as an independent layer, it must still have some relation with the underlying columns. The pore mouth is often wide and sealed with material of an organic nature containing protein and sugars (Tyler & Simkiss 1958, Cooke & Balch 1970, which is of true cuticular origin. Cuticular material may often dip into the pore mouth.…”
Section: Poresmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been invoked as evidence for the structural function of maculation in the mechanism compensating for Ca deficiency and/or strengthening the eggshell (see Cherry and Gosler 2010). However, there is an important, hitherto overlooked, issue directly linked to this physiological association between eggshell thinning and the presence of maculation-namely, the distribution and volume or thickness of the protoporphyrin layer over the eggshell surface (see Harrison 1966, Tyler 1969discussed in Maurer et al 2011b, Sparks 2011, a generality that must be universally applicable to all birds (cf. Reynolds et al 2009).…”
Section: Appendix the Structural Function Of Eggshell Maculation: A Smentioning
confidence: 99%
“…However, the distribution of the protoporphyrin layer(s) is not uniform and varies between different orders or even within a single egg. The spots of dark pigment may be present in the surface layer of the eggshell and/or at varying depths within the eggshell; in the the latter case, spots may not be visible on the surface (Harrison 1966, Tyler 1969, Jagannath et al 2008). Hence, not all maculation may have a structural function (Cherry andGosler 2010, Maurer et al 2011b).…”
Section: Appendix the Structural Function Of Eggshell Maculation: A Smentioning
confidence: 99%